William Samuel Johnson papers - Johnson, William Samuel, 1727-1819.
Correspondence; drafts of Johnson's first and second Connecticut addresses (1765) to George III, King of Great Britain; and drafts and copies of documents prepared during his service in the Stamp Act Congress, the Continental Congress, and the Constitutional Convention of 1787. Includes draft copies of the U.S. Constitution annotated by Johnson and William Jackson. Correspondents include Roger Alden, Montfort Browne, John Fitch, Samuel Huntington, and Christopher Leffingwell.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Statesman, jurist, and educator.
Collection material in English.
Keywords: Alden, Roger, -- 1754-1836 -- Correspondence; Browne, Montfort -- Correspondence; Fitch, John, -- 1743-1798 -- Correspondence; George -- III, -- King of Great Britain, -- 1738-1820.; Huntington, Samuel, -- 1731-1796 -- Correspondence; Jackson, William, -- 1759-1828.; Leffingwell, Christopher, -- 1734-1810 -- Correspondence; Great Britain; United States; United States. -- Constitutional Convention -- (1787); United States. -- Continental Congress; Constitutions -- United States; Connecticut -- History -- Colonial period, ca. 1600-1775.; United States -- Politics and government -- 18th century; Statesmen